THE EFFECTIVENESS OF COMMUNICATIVE LANGUAGE TEACHING (CLT) METHOD TO IMPROVE STUDENTS SPEAKING SKILL - Ilyas S; Mujahidah Mujahidah; Yulie Asni (Al-Irsyad: Journal of Education Science, 2023)
Students in Indonesia may understand theories in learning English but struggle to put them into practice.This research was conducted at SMAN 7 SIDRAP and the researcher wants to use Communicative Language Teaching (CLT) method which emphasizes language as a tool for communication, the researcher wanted to compare the CLT method with the conventional method that teachers usually use at school, so the formulation of the problem in this study was to find out whether there were differences in learning outcomes between the CLT method and the conventional method.This study aimed to assess the effectiveness of the Communicative Language Teaching (CLT) method in improving the speaking ability of students at SMAN 7 SIDRAP. This research used experiment design with Quasi experimental, the total sample was 40 students  that devided in 2 class that is 20 students’ was from 10 MIPA 1 as an Experiment class and another 20 was from 10 MIPA 2 as an Control Class, the result showed that the independent sample t-test revealed a significant difference between the two methods, with the CLT method being more effective in improving students' speaking abilities.